A Model for the Transfer of Perceptual-Motor Skill Learning in Human Behaviors - Rosalie, Simon; Müller, S. (American Alliance for Health, 2012)
This paper presents a preliminary model that outlines the mechanisms underlying the transfer of perceptual-motor skill learning in sport and everyday tasks. Perceptual-motor behavior is motivated by performance demands and evolves over time to increase the probability of success through adaptation. Performance demands at the time of an event create a unique transfer domain that specifies a range of potentially successful actions. Transfer comprises anticipatory subconscious and conscious mechanisms. The model also outlines how transfer occurs across a continuum, which depends on the individual’s expertise and contextual variables occurring at the incidence of transfer.